2007
DOI: 10.1016/j.visres.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual search training in subjects with severe to profound low vision

Abstract: Effects of practicing on feature search tasks (a 2 degrees square target amid 1 degrees square distracters) for 5 days were compared between 45 visually impaired (VI) subjects with severe to profound low vision and 23 age-matched normal controls (NV). Search accuracy and speed improved in both groups. VI subjects had larger training gains than NV subjects, but their proportional gains were similar to that of NV subjects. There were no significant differences in training effect at different set sizes in both gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…However, the observed 3-fold magnitude of impairment is functionally important, as such visual search deficits are likely to have a substantial effect on a wide range of visual functions. 52 It is likely that large field of view (~608) and the use of naturalistic cluttered scenes contributed to the observed magnitude of impairment. In adults with low vision, visual search defects worsen with both increasing search field size and increasing object density.…”
Section: Impaired Visual Search In Low Visionmentioning
confidence: 99%
“…However, the observed 3-fold magnitude of impairment is functionally important, as such visual search deficits are likely to have a substantial effect on a wide range of visual functions. 52 It is likely that large field of view (~608) and the use of naturalistic cluttered scenes contributed to the observed magnitude of impairment. In adults with low vision, visual search defects worsen with both increasing search field size and increasing object density.…”
Section: Impaired Visual Search In Low Visionmentioning
confidence: 99%
“…For typically-sighted individuals, perceptual learning can improve a wide range of visual abilities, including perception of motion, orientation, spatial frequency, as well as vernier acuity, identification of objects, visual search and face perception12. Visually impaired youth and adults also show evidence of perceptual learning, including improved contrast sensitivity, acuity thresholds, feature search and reading speeds567.…”
mentioning
confidence: 99%
“…The latter claim was based on success using a feature search paradigm in persons with severe to profound visual impairment. [22][23][24]31] Our experiments are among the few that have investigated the effect of parafoveal scotoma on functional visual performance. Like a central scotoma which clearly impairs visual performance, [8-10; 27-29] our results indicate that a relatively small parafoveal scotoma can also have a significant impact.…”
Section: Discussionmentioning
confidence: 99%
“…[21] The impetus for this study was based on studies of feature search in visually impaired adults with central and/or peripheral visual field loss. [22][23][24] Those studies found that persons with visual field loss, even severe loss, could perform a feature search task, but did so more slowly than persons with normal vision. [22,23] In addition, plots of RT for hits as a function of target location on the search grid revealed regions of elevated RT that roughly corresponded to areas of visual field loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation